Validity and Reliability of Customer Loyalty Instruments at Bank Jatim Sub-Branch Karangjati Ngawi - Oksatana, Miga; Mujanah, Siti; Fianto, Achmad Yanu Alif (International Journal of Economics (IJEC), 2025)
This study aims to assess the accuracy of the questionnaire measuring the customer loyalty instrument at Bank Jatim Sub-Branch Karangjati Ngawi using validity and reliability tests. The validity assessment is conducted to ascertain whether the questions on the questionnaire measure what is to be measured. The purpose of the reliability test is to gauge how trustworthy or dependable the questionnaire is. In this study, partial least squares (PLS) analysis is used to analyze data utilizing quantitative research methodologies. The study's sample used probabilty sampling using simple random sampling method as many as 46 respondents. Method of gathering data using a questionnaire. The findings indicate the validity value in the loading factor parameter in accordance with the criteria above 0.70. With AVE parameters (convergent validity) in accordance with the criteria above 0.50, and with discriminant parameters (Fornell Lacker, HTMT, cross loading) showing in accordance with the criteria below 0.90. Then the reliability value in all parameters (Croncbach's alpha and composite reliability) also shows in accordance with the criteria above 0.70. Thus this study proves that the questionnaire used to measure the level of customer loyalty at Bank Jatim Sub-Branch Karangjati Ngawi is valid and reliable.